2013
DOI: 10.1590/s1517-83822013000300028
|View full text |Cite
|
Sign up to set email alerts
|

Integron mediated multidrug resistance in extended spectrum beta-lactamase producing clinical isolates of Klebsiella pneumoniae

Abstract: The present study describes integron mediated multiple antibiotic resistance in extended-spectrum β-lactamase producing clinical isolates of Klebsiella pneumoniae. One hundred and four clinical isolates of K. pneumoniae from two Iranian hospitals were screened for extended-spectrum β-lactamase production and susceptibility of the extended-spectrum β-lactamase producing isolates was determined to 17 antibiotics by disc diffusion. Presence of integron classes 1, 2 and 3 was detected by PCR and integrase specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…11,47 Since, only a rare studies about class 3 integron has been described and categorized 10,48,50 Mobarak-Qamsari et al, described 22 (44%) integron class 1, only 3 (6%) isolates of K. pneumoniae carried integron class 2 and none of them contained of integon class 3. 51 Possible critical role of integrons genes in distribution of ESBL-encoding bla TEM gene among ESBL-producing K. pneumoniae clinical isolates may be inferred. This highpoints the increasing complication of antimicrobial agent resistance problems, and the explanations for this condition need further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…11,47 Since, only a rare studies about class 3 integron has been described and categorized 10,48,50 Mobarak-Qamsari et al, described 22 (44%) integron class 1, only 3 (6%) isolates of K. pneumoniae carried integron class 2 and none of them contained of integon class 3. 51 Possible critical role of integrons genes in distribution of ESBL-encoding bla TEM gene among ESBL-producing K. pneumoniae clinical isolates may be inferred. This highpoints the increasing complication of antimicrobial agent resistance problems, and the explanations for this condition need further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…Class III integrons have been reported only in very few studies 14,62,63 . MobarakQamsari et al 64 identified 22 (44%) class I integron-carrying K. pneumoniae isolates, but only three (6%) of the isolates had class II integrons and none contained class III integrons 64 . These findings suggest that class I integron genes may play a critical role in the distribution of β-lactamase-encoding genes among clinical β-lactamase-producing K. pneumoniae isolates.…”
Section: -59mentioning
confidence: 99%
“…Several reports stated that the presence of integrons in ESBL coding gene plasmid has a high correlation with MDR. This may occur if the ARI and ESBL coding genes are within one integron complex or within one plasmid [11,12].…”
Section: Introductionmentioning
confidence: 99%